2018
DOI: 10.1096/fj.201801894r
|View full text |Cite
|
Sign up to set email alerts
|

Cystathionine γ‐lyase deficiency aggravates obesity‐related insulin resistance via FoxO1‐dependent hepatic gluconeogenesis

Abstract: Hepatic gluconeogenesis makes a significant contribution to the pathogenesis of obesity and its related insulin resistance. Cystathionine γ‐lyase (CSE; also cystathionase), a principal hydrogen sulfide (H2S)‐synthesizing enzyme in the liver, is involved in glucose and lipid metabolism disorders. However, the roles and precise mechanisms of CSE/H2S in obesity and its related insulin resistance remain obscure. Here we show that CSE knockout exacerbated high‐fat diet—induced mouse obesity as well as its related i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 57 publications
(64 reference statements)
0
19
0
Order By: Relevance
“…Guo et al indicated that CSE knockout promoted HFD-induced mouse obesity and insulin resistance and increased hepatic gluconeogenesis. A low dose of NaHS treatment (25 μmol/kg/d, intraperitoneally for 12 weeks) improved HFD-induced obesity and insulin resistance but a high dose of NaHS treatment (50 μmol/kg/d, intraperitoneally for 12 weeks) promoted HFD–induced obesity and insulin resistance [35] . Treatment with H 2 S gas buffer, or the H 2 S donor GYY4137 improved insulin resistance in HFD-induced obese mice [43] .…”
Section: H 2 S and Hypothalamusmentioning
confidence: 97%
See 2 more Smart Citations
“…Guo et al indicated that CSE knockout promoted HFD-induced mouse obesity and insulin resistance and increased hepatic gluconeogenesis. A low dose of NaHS treatment (25 μmol/kg/d, intraperitoneally for 12 weeks) improved HFD-induced obesity and insulin resistance but a high dose of NaHS treatment (50 μmol/kg/d, intraperitoneally for 12 weeks) promoted HFD–induced obesity and insulin resistance [35] . Treatment with H 2 S gas buffer, or the H 2 S donor GYY4137 improved insulin resistance in HFD-induced obese mice [43] .…”
Section: H 2 S and Hypothalamusmentioning
confidence: 97%
“… Action Cells/Model H 2 S gas/donor application (concentration) Effects Refs. Glucose uptake In vitro study HepG2 cells/primary mouse hepatocytes NaHS (10, 30 and 100 μM)/– Inhibited [32] Glycogen storage In vitro study HepG2 cells NaHS (10, 30 and 100 μM) Inhibited [32] In vivo study Liver from mice under nonfastingor 6-h fasting condition Inhibited [32] Gluconeogenesis In vitro study HepG2 cells/primary mouse hepatocytes NaHS (10, 30 and100 μM)/– Promoted [32] Primary mouse hepatocytes NaHS (30 μM) Promoted [33] HepG2 cells/primary mouse hepatocytes NaHS (50 μM)/– Promoted [34] HepG2 cells/primary mouse hepatocytes NaHS (100 μM)/– Inhibited [35] In vivo study Pyruvate tolerance test on overnight-fasted mice NaHS (39 and 63 μM/kg) Promoted [33] Pyruvate tolerance test on high fat diet-fed mice NaHS (50 μM/kg/day) Inhibited [35] Mitochondrial function Biogenesis Primary moue hepatocytes NaHS (30 μM) Promoted [38] Bioenergetics HepG2 cells NaHS (0.01 and 0.1 μM) Promoted …”
Section: Hydrogen Sulfide Regulates Insulin Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, other data report that H 2 S suppresses hepatic gluconeogenesis, thus supporting its potential usefulness in the pharmacotherapy of T2DM. In particular, Guo and colleagues (Guo et al, 2019) showed that global CSE deficiency aggravates obesity‐induced insulin resistance by promoting hepatic gluconeogenesis in mice, probably by inhibition of the AMPK signaling pathway and increase in nuclear accumulation of forkhead boxprotein O1 (FoxO1). Accordingly, daily treatment with NaHS for 12 weeks (25 μmol/kg/day, i.p) reversed these effects, partially restoring physiological H 2 S concentrations in the liver.…”
Section: Hydrogen Sulfidementioning
confidence: 99%
“…This finding further supports the hormetic theory of H 2 S, which states that low levels of H 2 S are beneficial while high levels may be detrimental for health (Hua, Zhou, & Gong, 2013). Furthermore, silencing of CSE in hepatic cells (HepG2) significantly reduced the inhibitory effect promoted by insulin on gluconeogenesis, while NaHS (100 μM) fully restored the control of insulin on hepatic glucose production in these cells (Guo et al, 2019). Noteworthy, decreased CSE activity has been also recorded both in livers of diabetic rats and peripheral blood mononuclear cells of diabetic patients (Manna et al, 2014).…”
Section: Hydrogen Sulfidementioning
confidence: 99%